ИНСТИТУТ ПРАВ И СВОБОД ЧЕЛОВЕКА И ГРАЖДАНИНА: НЕКОТОРЫЕ ТЕОРЕТИЧЕСКИЕ АСПЕКТЫ (Journal of actual problems of jurisprudence, 2019)
The role of needs in human development, society is great, which is increasingly proven in the science ofhuman, both natural and humanitarian, first of all, psychology, social psychologyin particular, sociology. The role of needs is also justified in the work of individual lawyers.The relationship between needs and law is seen in the fact that the roots of law go deep into production,consumption and human needs. So, Professor D. Kerimov notes that the right asa specific tool that helps to meet the typical needs of a person canto exist and act only if there is an objective commonality in the system of needsindividuals [9, p. 4].